Generation of orbital angular momentum in a C-band laser - Mellon, Samuel N.; Younts, Robert A.; Johnson, Eric (SPIE, 2022)
The generation of orbital angular momentum (OAM) in laser light has been the subject of study for various applications including the improvement of laser transmission in turbid environments. NIWC Atlantic has collaborated with Clemson University to build an experiment to test rapidly tunable OAM system for higher order Bessel beams integrated in time (HOBBIT) and OAM cross-correlator at the communications C-band. This report details the construction of the bench prototype and summarizes future research avenues.